The application of the prescibed minimum sentence in terms of the Criminal Law Amendment Act, 105 of 1997 on child offenders charged with serious crimes - Boroto, Mathobela Lesetja Frans (My University, 2008)
The Constitution of the Republic of South Africa 108 of 1996 has brought about an inspiration for the development of our legal system. Youthful offenders like any other person in South Africa have fundamental rights. Section 28 provides for the rights of children in general and section 28(2) makes provisions for the supremacy of children’s rights in every field of the law. With regard to child offenders charged with serious crimes, courts and all those dealing with them need to take their basic rights into account. Courts should observe the rules and procedures of fair trial in order to protect and promote the individual or group of child offender’s rights. Courts are enjoined to act dynamically to obtain full particulars of the child offender’s personality and personal circumstances, and to engage the services of the probation officers or correctional service officials. The Constitution of the Republic of South Africa Act 108 of 1996, the Child Care Act 74 of 1983 and 38 of 2005, Criminal Law Amendment Act 105 of 1997, Criminal Procedure Act 51 of 1977, etc regulate and guide courts in dealing with children who fall foul of the law. Firstly, I am indebted to Mrs. A.T Thoka, and Prof. Scheepers my supervisors who unselfishly assisted and encouraged me through the maze I had to go through this dissertation. I would also like to express my gratitude to the late Mrs Motimele Mapula Rebecca, my wife Ramadimetja Teresiah, my daughter Isabel Madithotsana Mokonyama and my two sons Mokitlelo and Matsimela to whom this short dissertation is dedicated for their kindness in allowing me to use their quality time for my personal advancement. Last, but not least, my thanks are extended to Ms Makgatho Jerminah for having typed and compiled this dissertation.
Thesis (LLM) -- University of Limpopo, 2008
Keywords: Criminals; Child offenders; Criminal law; Juvenile delinquents; Criminals